Micronutrient Antioxidants for Men (Menevit®) Improve Sperm Function by Reducing Oxidative Stress, Resulting in Improved Assisted Reproductive Technology Outcomes - Seiji Ogawa; Kuniaki Ota; Kaori Nishizawa; Masumi Shinagawa; Mikiko Katagiri; Hiroyuki Kikuchi; Hideyuki Kobayashi; Toshifumi Takahashi; Hiroaki Yoshida (MDPI AG, 2024)
Oxidative stress (OS) affects men's health and impairs spermatogenesis. Micronutrient antioxidants are available for male infertility as complemental support; however, their efficacy remains debatable. This study aimed to investigate whether antioxidants can help to reduce sperm OS and improve semen analysis and quality. We included 171 male partners of couples planning to undergo assisted reproductive technology (ART). Male partners, aged 29-41 years, of couples intending to conceive were self-selected to take daily antioxidants (n = 84) containing folic acid and zinc, or not to take antioxidants (n = 52) for 6 months. We analyzed the alterations in serum oxidant levels, sperm parameters, OS, and deoxyribonucleic acid fragmentation after 3 and 6 months. Additionally, implantation, clinical pregnancy, and miscarriage rates after vitrified-warmed embryo transfer were compared between those taking antioxidants and those not taking them after 6 months. In men with high static oxidation-reduction potential (sORP), we observed a significant improvement in sperm concentration and sORP. The high-quality blastocyst rate tended to increase, and implantation and clinical pregnancy rates also significantly increased after 6 months of intervention. The micronutrient antioxidants could improve sperm function by reducing OS and improving ART outcomes. Therefore, micronutrient antioxidants may be a viable treatment option for male infertility.